AB0902 Risk Factors of Osteoporosis in Hemodialysis Patients. (9th June 2015) - Slouma, M.; Sahli, H.; Rekik, S.; Smaoui, W.; Boussaid, S.; Bahlous, A.; Laadhar, L.; Cheour, E.; Ben Moussa, F.; Sallami, M.; Elleuch, M.
Abstract : Background: Low bone mass is common in patients undergoing hemodialysis. Osteoporosis can be associated with serious bone health problems, especially fragility fractures. Objectives: The aim of the study was to determine the frequency of osteoporosis in hemodialysis Tunisian patients and to identify the risk factors of low bone mass in this population. Methods: We conducted a cross-sectional study over a period of 4 years [2009-2012] including 90 hemodialysis. Blood samples were drawn before hemodialysis session from patients. We measured calcium, phosphate, alkaline phosphatase (ALP) and intact parathyroid hormone (PTH). Bone mass density (BMD) was measured by dual energy X-ray absorptiometry (DXA) at the lumbar spine and total hip. Using WHO criteria as a cutoff point, osteopenia was defined as a T-score lower than -1 and osteoporosis was defined as a T-score lower than -2.5. All statistical analysis were performed using the Windows SPSS 19 package. Results: Ninety patients were included: 58 male (64%) and 32 female (36%). The mean age was 53.01±14.60 years. The mean age of onset of hemodialysis was 50.06±14.82 years. Serum calcium and phosphorus levels were respectively at 2.084±0.32 mmol/L and 1.84±0.57 mmol/L. The average rates of PTH and ALP were respectively at 425.70±380.78 pg/mL and 88.35±72.56 UI/L. Fifty six percent of patients have PTH values between 2 and 9 times the upper normal limit of the assay as recommended by KDIGO (Kidney Disease: Improving Global Outcomes). However, 19% of patients have PTH values less than 2 times the upper normal limit of the assay. The mean of BMD was 0.854±0.152 g/cm 2 in the hip and 1.155±0.218 g/cm 2 in the lumbar spine. Twenty three percent of patients have osteoporosis and 45% have osteopenia. Osteoporosis affected the hip (20%) more than the spine (5.5%). Regarding risk factors, femoral BMD had significant negative correlations with the with the following parameters: age (r:-0.289; p:0.006), age of onset of hemodialysis (r:-0.359; p:0.001) and PTH level (r:-0.275; p:0.009). However, no correlations was found between lumbar spine BMD and the following parameters: age, age of onset of hemodialysis, calcium, phosphorus and PTH level. Conclusions: Our study showed that osteoporosis is common in dialysis patient [1]. The most common region of bone loss was the hip. The decrease in cortical BMD was associated with advanced age, age of onset of hemodialysis and elevated levels of PTH [2]. References: Nybo M, Jespersen B, Aarup M, Ejersted C, Hermann AP, Brixen K. Determinants of bone mineral density in patients on haemodialysis or peritoneal dialysis–across-sectional, longitudinal study. Biochem Med. 2013;23(3):342-50. Huang GS, Chu TS, Lou MF, Hwang SL, Yang RS. Factors associated with low bone mass in the hemodialysis patients–a cross-sectionalcorrelation study. BMC Musculoskelet Disord. 2009; 4;10:60. Disclosure of Interest: None declared